Performance Evaluation of Adverse Atmospheric Effects on Free Space Optical Communication - Ganesh N. Gaikwad; Ishwar Nivasrao Mundhe; Khushi Gopaldutt Nagaich; Nidhi Mishra (International Journal of Solid State Innovations & Research, 2024)
There is an increasing need for communication systems that can accommodate high bandwidth and quick data transfer rates in today's fast-paced technological environment. Free Space Optical (FSO) communication has become a very attractive technology to address these changing needs. FSO systems, which use license-free infrared beams, have a number of benefits, including strong bandwidth, immunity to interference, improved security, and small, light designs. FSO is used in many different applications, such as voice, video, and data transmission. It allows laser beams to be transferred between transceivers to enable point-to-point connectivity. Despite all of its advantages, climatic circumstances can affect the efficacy of FSO, especially when it comes to keeping connections in line of sight during bad weather. Free Space Optical Communication (FSOC) is a promising technology that uses optical signals to transmit data through the atmosphere, which can provide high bandwidth, low latency, and high security compared to other wireless communication technologies. However, atmospheric conditions such as fog, rain, and turbulence can cause attenuation, scattering, and beam wander, which can degrade the quality and reliability of data transmission. To overcome this major problem, several techniques like resending the data, sending through other route, or using Multiple in Multiple Out (MIMO) systems are used.
Keywords: FSOC; MIMO; high bandwidth; high security; low latency